Analisis Hubungan Antara Kecerdasan Emosional dengan Hasil Belajar pada Materi Pecahan di SD Al-Maksum Balunganyar - Fitriyatul Badriyah; Andika Setyo Budi Lestari; Ani Afifah (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
In an educational context, especially in mathematics learning, emotional intelligence can play a significant role in how students face challenges, deal with stress, and interact with classmates and teachers. Students with high emotional intelligence tend to have better strategies for managing their feelings, which can help them stay focused, motivated, and more open to learning. This research uses a quantitative descriptive method with a correlational approach, namely research that determines the relationship between two or more variables with a symmetrical relationship. The quantitative descriptive method is a research method that aims to describe a situation objectively using numbers. Thus, there is a significant positive relationship between emotional intelligence and the mathematics learning outcomes of fifth grade students at SD Al-maksum Balunganyar. These results are shown by Fcount Ftable, namely 3.24 2.48. The R2 value is 0.0939.3%, this can be stated that the contribution of emotional intelligence to the mathematics results of grade 5 students at SD Al-maksum Balunganyar is 9.3%, the rest is influenced by other factors. The prerequisite test shows that the two variables are normally distributed . Using simple regression, a significant positive relationship was found between emotional intelligence and the mathematics learning outcomes of fifth grade students at SD Al-maksum Balunganyar at 9.3%.